Fault Effect Modeling in a Heterogeneous SystemC Based Virtual Platform Framework for Cyber Physical Systems - Becker, Markus; Kuznik, Christoph; Müller, Wolfgang
This paper presents an advanced eight levels spanning SystemC based virtual platform methodology and framework - referred to as HeroeS 3 - providing smooth application to platform mapping and continuous co-refinement of a virtual prototype with its physical environment model. For heterogeneity support, various SystemC extensions are combined covering continuous/discrete models of computation and different communication abstractions, such as analog mixed-signal models, abstract RTOS/HAL/middleware models, TLM bus models, and QEMU wrappers. We enable dependability assessment by Fault Effect Modeling (FEM) at the virtual prototype in order to avoid risking physical injury or damage. Also, simulation results are deterministic and can be evaluated interactively or offline. We apply FEM to both the physical environment model and the different abstractions of the virtual prototype. Currently, we focus on sensor failures and application control flow errors.
Keywords: Computational modeling; Finite element analysis; Prototypes; Abstracts; Software; Fault tolerance; Fault tolerant systems

An Approach for Self-Reconfiguring and Fault-Tolerant Distributed Real-Time Systems - Klobedanz, Kay; Müller, Wolfgang; Rettberg, Achim
In this paper we present an approach for the self reconfiguration of distributed micro-controllers for increased fault tolerance. Based on a modified distributed system topology utilizing a time division multiple access (TDMA) protocol, i.e., Flex Ray, we present a self-organized distributed coordinator concept which performs the self-reconfiguration in the case of node failures. We introduce a distributed coordinator, which utilizes redundant slots in the Flex Ray communication schedule and combines messages in configured protocol frames and slots to avoid a complete bus restart. As such, the self-reconfiguration is realized by means of predetermined information about resulting changes in the communication dependencies and (re-)assignments determined in the design phase. To retrieve the necessary information, we present an analytical approach, which determines a combined solution for the initial configuration and all possible reconfigurations for the remaining nodes of the Flex Ray network in case of node failures. Hence, through this method we can design self-reconfiguring network-based systems enabling the handling of node failures for an increased fault tolerance.
Keywords: Real time systems; Fault tolerant systems; Schedules; Protocols; Redundancy; Delay

A Reconfiguration Approach for Faul-Tolerant FlexRay Networks - Klobedanz, Kay; König, Andreas; Müller, Wolfgang (Proceedings of DATE'11)
In this paper we present an approach for the configuration and reconfiguration of FlexRay networks to increase their fault tolerance. To guarantee a correct and deterministic system behavior, the FlexRay specification does not allow a reconfiguration of the schedapproachule during run time. To avoid the necessity of a complete bus restart in case of a node failure, we propose a reconfiguration using redundant slots in the schedule and/or combine messages in existing frames and slots, to compensate node failures and increase robustness. Our approach supports the developer to increase the fault tolerance of the system during the design phase. It is a heuristic, which, additionally to a determined initial configuration, calculates possible reconfigurations for the remaining nodes of the FlexRay network in case of a node failure, to keep the system working properly. An evaluation by means of realistic safety-critical automotive real-time systems revealed that it determines valid reconfigurations for up to 80% of possible individual node failures. In summary, our approach offers major support for the developer of FlexRay networks since the results provide helpful feedback about reconfiguration capabilities. In an iterative design process these information can be used to determine and optimize valid reconfigurations.
Keywords: Schedules; Fault tolerant systems; Redundancy; Protocols; Automotive engineering; Genetic algorithms

Distributed Coordination of Task Migration for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; Defo, Gilles B.; Müller, Wolfgang; Kerstan, Timo (Proceedings of SIES 2010)
In this paper we present an approach to increase the fault tolerance in FlexRay networks by introducing backup nodes to replace defect ECUs (Electronic Control Units). In order to reduce the memory requirements of such backup nodes, we distribute redundant tasks over different nodes and propose the distributed coordinated migration of tasks of the defect ECU to the backup node at runtime. This approach enhances our former work in, where we extended the FlexRay bus schedule by redundant slots to consider changes in the communication/slot assignment and investigated and evaluated different solutions to migrate the redundant tasks to the backup node using the static and/or dynamic segment of the communication cycle for transmissions. We present the approach of distributed coordination for migration and communication instead of additional dedicated coordinator nodes to further increase the fault tolerance. With this approach we improve the safety of FlexRay networks by avoiding a possible single point of failure due to a dedicated coordinator node also minimizing the necessary time needed for a reconfiguration after an ECU failure. Furthermore, we reduce the overhead within the communication and the demand for additional hardware components.
Keywords: Fault tolerant systems; Protocols; Redundancy; Runtime; Payloads; Schedules